2017
DOI: 10.1007/s00198-017-4137-6
|View full text |Cite
|
Sign up to set email alerts
|

Value and potential limitations of vertebral fracture assessment (VFA) compared to conventional spine radiography: experience from a fracture liaison service (FLS) and a meta-analysis

Abstract: SummaryWe evaluated the value of VFA in the identification of vertebral fractures using a retrospective study and a meta-analysis. Performance of VFA was adequate in the meta-analysis although this was not demonstrated in our centre. We recommend checking the performance of VFA tools before exclusively relying on this tool.IntroductionVertebral fractures are traditionally diagnosed using conventional radiographs of the spine. Vertebral fracture assessment (VFA) has been advocated as an alternative tool in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In Canada, Manitoba is the only province that currently systematically employs VFA as part of their provincial bone densitometry and fracture assessment protocols. VFA at the time of bone densitometry is inexpensive, convenient, point‐of‐care testing with minimal patient radiation exposure and minimal added bone technologist time commitment to perform . Our study and others have shown that bone density technologists can successfully implement a decision rule to identify those referred for bone densitometry as also appropriate candidates for VFA.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In Canada, Manitoba is the only province that currently systematically employs VFA as part of their provincial bone densitometry and fracture assessment protocols. VFA at the time of bone densitometry is inexpensive, convenient, point‐of‐care testing with minimal patient radiation exposure and minimal added bone technologist time commitment to perform . Our study and others have shown that bone density technologists can successfully implement a decision rule to identify those referred for bone densitometry as also appropriate candidates for VFA.…”
Section: Discussionmentioning
confidence: 68%
“…VFA at the time of bone densitometry is inexpensive, convenient, point-of-care testing with minimal patient radiation exposure and minimal added bone technologist time commitment to perform. (13,(41)(42)(43)(44) Our study and others (19,42) have shown that bone density technologists can successfully implement a decision rule to identify those referred for bone densitometry as also appropriate candidates for VFA. Prior studies that have shown that clinicians can be easily trained to identify vertebral fractures on lateral spine images.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 88%
See 1 more Smart Citation
“…Vertebral fracture assessment is one of the substantial additional methods of bone tissue appraisal in patients with osteoporosis [1,[16][17][18]. According to Genant's classification [19] which is based on the vertebral shape with respect to vertebral height loss and included in DXA software, the loss of >25% of vertebral height (anterior, posterior, and/or middle) is confirmed as moderate and severe VDs (grades 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…e investigator confirmed the fracture history according to medical source. Vertebral fractures were affirmed by vertebral fracture assessment (VFA) which was performed additionally to BMD measurements by DXA on the lateral VFA images of the spine [16][17][18]. During this procedure, the patient was in supine position and a cushion supported the knees.…”
Section: Bone Mineral Density and Vertebral Fracturesmentioning
confidence: 99%